Stereoregular [m,n]-polyurethanes derived from D-mannitol - Fidalgo, Daniela Marina (2013)
Novel linear carbohydrate-derived [m,n]-polyurethanes are successfully prepared using D-mannitol as renewable and low cost starting material. The key comonomer, 1,6-di-O-phenylcarbonyl-2,3,4,5-tetra-O-methyl-D-mannitol is polymerized with a diamine synthesized from D-mannitol or with alkylenediamines. These polymerization reactions afford, respectively, a [6,6]-polyurethane entirely based on a carbohydrate derivative or [m,n]-polyurethanes constituted by a poly-O-methyl substituted unit alternating with a polymethylene chain. All these polymers are stereoregular, as result of the C2 axis of symmetry of mannitol. The optically active polyurethanes are characterized by standard methods (FTIR, RMN, GPC, TGA, and DSC). Thus, GPC analysis reveals weight-average molecular weights between 18,000 and 25,000 Da. Thermal studies (DSC) indicate that the polymers obtained are amorphous materials with Tg values dependent on the structure and chain length of the diamine constituent.